1995
DOI: 10.1111/j.1570-7458.1995.tb01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant effects of plant lectins and an enzyme on the adult stage of the rice brown planthopper, Nilaparvata lugens

Abstract: The feeding activity of adult rice brown planthopper, Nilaparvata lugens (St/~l) on selected proteins incorporated into artificial diets was examined, based on quantitative analysis of honeydew excretion, in order to determine the mechanism of action of antimetabolic proteins towards homopteran pests. The lectins Galanthus nivalis agglutinin (GNA), wheat germ agglutinin (WGA) and the enzyme soybean lipoxygenase (LPO), previously demonstrated to be toxic to this insect, reduced honeydew excretion levels of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 22 publications
1
61
2
Order By: Relevance
“…But no GNA was detected in the honeydew. This is in contrast to Powell et al (1995a) who demonstrated the excretion of GNA by N. lugens fed on an artificial diet containing a high lectin concentration. It can be hypothesized that as soon as GNA-binding sites in the insect have been saturated, excess GNA-intake can be excreted in the honeydew.…”
Section: Gna: a Mannose-specific Lectin With Negative Effects On Sevecontrasting
confidence: 50%
See 2 more Smart Citations
“…But no GNA was detected in the honeydew. This is in contrast to Powell et al (1995a) who demonstrated the excretion of GNA by N. lugens fed on an artificial diet containing a high lectin concentration. It can be hypothesized that as soon as GNA-binding sites in the insect have been saturated, excess GNA-intake can be excreted in the honeydew.…”
Section: Gna: a Mannose-specific Lectin With Negative Effects On Sevecontrasting
confidence: 50%
“…Although responses varied substantially over the studies, GNA had a markedly negative effect on several aspects of insect life. Powell et al (1995a) showed a dose-dependent effect of GNA on honeydew production (a common measure for the amount of feeding in hemipteran insects) of the brown plant hopper (Nilaparvata lugens). After feeding GNA to the insects at doses between 0.01 and 0.1% (w/v), the presence of the lectin in the honeydew of GNA-fed insects was demonstrated.…”
Section: Gna: a Mannose-specific Lectin With Negative Effects On Sevementioning
confidence: 99%
See 1 more Smart Citation
“…Lectins from snowdrop, pea, wheat, rice, castor, soybean, mungbean, garlic, sweet potato, tobacco, chickpea and groundnut have been isolated and characterised. Lectins produce chronic effects on survival and development of insect pests elonging to different insect orders (Shukle and Murdock, 1983;Czapla and Lang, 1990;Habibi et al 1992;Powell et al 1995). Transgenic tobacco expressing pea lectin has shown adverse effects against H. virescens (Boulter et al 1990).…”
Section: Plant Lectinsmentioning
confidence: 99%
“…Insecticidal properties of lectins have been reported in a number of studies against various insects such as European corn borer (Ostrinia nubilalis), homopeterans, leidopterans and coloeopterans. Studies have shown that lectins affect survival and development of insects (Powell et al, 1995). Lectins attach to the glycosylated receptors present on the lining of insect's gut.…”
Section: Introductionmentioning
confidence: 99%